At least two molecules of the RNA helicase Has1 are simultaneously present in pre-ribosomes during ribosome biogenesis - Gnanasundram, Sivakumar Vadivel; Koš-Braun, Isabelle C.; Koš, Martin (Nucleic acids symposium series, 2019)
The RNA helicase Has1 is involved in the biogenesis of both small and large ribosomal subunits. How it performs these separate roles is not fully understood. Here we provide evidence that at least two molecules of Has1 are temporarily present at the same time in 90S pre-ribosomes. We identified multiple Has1 binding sites in the 18S, 5.8S and 25S rRNAs. We show that while the Has1 catalytic activity is not required for binding to 5.8S/25S region in pre-rRNA, it is essential for binding to 18S sites. After the cleavage of pre-rRNA at the A2 site, Has1 remains associated not only with pre-60S but, unexpectedly, also with pre-40S ribosomes. The recruitment to 90S/pre-40S and pre-60S ribosomes is mutually independent. Our data provides insight into how Has1 performs its separate functions in the synthesis of both ribosomal subunits.